Roman settlement pattern and LCP modelling in ancient North-Eastern Pannonia (Hungary) - Bence Simon (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae, 2016)
Roman times are known as an epoch when man subdued nature all over the orbis terrarum, however all humans were and are still bound by certain environmental conditions, therefore in settling a special dichotomy can be observed. In my present study I am analysing the Roman settlement patterns of the North-Eastern part of Pannonia by evaluating field-walking material and results of excavations. The classification of the sites is mainly based on building material and pottery collected on the field. After examining the structure of settlements with the assistance of GIS technologies, I assess how the least cost paths calculated from the relief of terrain influenced settling.